2020
DOI: 10.3390/cancers12020282
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Complications in Chronic Lymphocytic Leukemia in the Era of Targeted Drugs

Abstract: Autoimmune phenomena are frequently observed in patients with chronic lymphocytic leukemia (CLL) and are mainly attributable to underlying dysfunctions of the immune system. Autoimmune cytopenias (AIC) affect 4–7% of patients with CLL and mainly consist of autoimmune hemolytic anemia and immune thrombocytopenia. Although less common, non-hematological autoimmune manifestations have also been reported. Treatment of CLL associated AIC should be primarily directed against the autoimmune phenomenon, and CLL specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 121 publications
(162 reference statements)
0
38
0
Order By: Relevance
“…The use of antileukemic drugs that inhibit Btk signaling to promote apoptosis of malignant B cells, especially in chronic lymphocytic leukemia, theoretically may also affect B cell selection by interfering with normal BCR signaling leading to the release of autoreactive B cells. Autoimmune cytopenias have been observed in patients with chronic lymphocytic leukemia treated with ibrutinib ( 123 , 124 ).…”
Section: The Role Of B Cell Mediated Autoimmunitymentioning
confidence: 99%
“…The use of antileukemic drugs that inhibit Btk signaling to promote apoptosis of malignant B cells, especially in chronic lymphocytic leukemia, theoretically may also affect B cell selection by interfering with normal BCR signaling leading to the release of autoreactive B cells. Autoimmune cytopenias have been observed in patients with chronic lymphocytic leukemia treated with ibrutinib ( 123 , 124 ).…”
Section: The Role Of B Cell Mediated Autoimmunitymentioning
confidence: 99%
“…Another consequence of the altered humoral immunity is the occurrence of autoimmune complications. Episodes of autoimmune cytopenia are frequently observed in CLL patients and are attributable to high affinity polyclonal IgG autoantibodies which are produced by the non-leukemic B cells and target membrane antigens expressed on red blood cells, platelets, or granulocytes [as reviewed in (17,151,152)]. In addition, we previously reported that polyclonal antibodies directed to recurrent antigens expressed by tumor cells can be frequently found in the serum of CLL patients, especially those with progressive disease.…”
Section: Humoral Immune Responsementioning
confidence: 99%
“…However, most of the immune surveillance dysfunctions accumulate during disease evolution, most likely constributing to the transition from MBL to CLL [as reviewed in (8,9)]. From the clinical standpoint, these immunologic dysregulations are responsible for the increased susceptibility to infections and secondary malignancies, the occurrence of autoimmune phenomena and the failure to control disease progression (10,11) [and as reviewed in (5,(12)(13)(14)(15)(16)(17)].…”
Section: Introductionmentioning
confidence: 99%
“…Since the number of platelets in the whole blood of healthy adults varies in a relatively wide range of 150-450•10 6 cells/mL, this factor must be taken into account in the production of all types of platelet concentrates [16]. In addition, in some diseases, including immune thrombocytopenia and chronic leukocyte leukemia, the platelet number in the blood is reduced to 100•10 6 cells/mL and less [41,42]. When studying the correlation between the platelets count in whole blood and in the prepared concentrates, the products were divided into two groups according to the number of platelets in the processed blood.…”
Section: Resultsmentioning
confidence: 99%